HEMATOLOGICAL FINDINGS IN COVID-19 AND INSIGHTS TO STEM CELL THERAPY - Ghada ELGohary (Elsevier, 2021)
Objective: As the COVID-19 was spreading to all countries, its manifestations were identifying gradually, which were related to several organs. COVID-19 is associated with distinct hematological changes, increased serum inflammatory markers, and coagulopathy. Methodology: Most of the known COVID 19 complications are related to the patients’ prognosis and mortality, particularly in those with severe disease, the issue which attract the scientists and the medical physicians all over the world to find the proper treatment for such monter, we discussed the associations between COVID-19 clinical features and complications, and secondly, its hematological findings and coagulopathy are investigated. Conclusions: Such associations not only may shed light on our prognostic view of patients with COVID-19 but also will entail significant therapeutic implications. One of its key implications is to utilize the mesenchymal stem cells (MSCs) to treat patients with COVID-19. Herein, this kind of novel therapy has been discussed, as well with its cons and pros points